Becoming posthuman: hepatitis C, the race to elimination and the politics of remaking the subject. Issue 3 (2nd September 2021) - Seear, Kate; Lenton, Emily
ABSTRACT: Hepatitis C has long been a public health problem in Australia. 'Revolutionary' new drugs with the potential to cure hepatitis C have now emerged. The Australian government has invested heavily in them, and has an ambitious goal to eliminate hepatitis C by 2030. Numerous shifts in policy and practice are required if the elimination agenda is to be realised. This paper explores the significance of these shifts. We ask: what is the race to elimination doing with the subject ? We argue that the race to elimination can be understood, simultaneously, as a product of posthuman forces, capable of being analysed using the theoretical tools made available via the posthuman turn; producing an intervention in what it means to be human; and generating a dilemma for people who use (or used) drugs, people with hepatitis C, and posthuman scholarship. In drawing out these issues, we aim to: trace the significant developments underway in hepatitis C medicine and raise awareness of them; encourage reflection on the consequences of these developments; and invite reflections on what might be lost when the human is remade by hepatitis C medicine.